2018
DOI: 10.7567/jjap.57.06hj05
|View full text |Cite
|
Sign up to set email alerts
|

Development of energy-harvesting system using deformation of magnetic elastomer

Abstract: In this paper, we propose a power generation method using the deformation of a magnetic elastomer for vibration energy harvesting. The magnetic flux lines in the structure of the magnetic elastomer could be markedly changed if the properly designed structure was expanded and contracted in a static magnetic field. We set a coil on the magnetic elastomer to generate electricity by capturing this change in magnetic flux flow. We fabricated a centimeter-scale device and demonstrated that it generated 10.5 mV of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In our previous works, we employed elastomer dispersed with magnetic particles. We developed energy harvesting systems [1][2][3], artificial cilia [4][5][6][7][8][9][10][11][12][13][14] and worm-like robots [15,16] using the magnetic soft material. We evaluated the motion of worm-like crawling robots and found that the interface between the robot and the substrate affected so much for the locomotion ability of the robot [15].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we employed elastomer dispersed with magnetic particles. We developed energy harvesting systems [1][2][3], artificial cilia [4][5][6][7][8][9][10][11][12][13][14] and worm-like robots [15,16] using the magnetic soft material. We evaluated the motion of worm-like crawling robots and found that the interface between the robot and the substrate affected so much for the locomotion ability of the robot [15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important components of soft robotics is the soft actuator or artificial muscle, therefore, several models that use photosensitive dielectric polymers [13][14][15], or ionic liquid-based gels [16] have been developed. Another approach is to use physical-based actuators, such as the pneumatic type actuators (the most popular one) [13,14], which are controlled by air pressure through an air tube, or magnetic actuators, which are composed of magnetic powder and a flexible matrix, such as an elastomer or a gel [6][7][8][9][10][11][12][19][20][21][22][23][24][25]. Furthermore, these physical actuators provide excellent responsiveness using external power sources.…”
Section: Introductionmentioning
confidence: 99%
“…If we could apply biomimicry structures of these natural cilia, they would be useful engineering tools. We utilized magnetic elastomer [7][8][9] to mimic the motion of flexible structures in natural cilia [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%